Management and Empowerment Model In LAZISMU Special Region of Yogyakarta - rifan, Akhmad Arif Rifan; Miftah Khilmi Hidayatulloh; Winda Safitri; Leni Kurnia Safitri; Maisha Madania (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This research aims to develop a comprehensive management and empowerment model for LazisMU in the Special Region of Yogyakarta (DIY). The study employs a qualitative approach, primarily utilizing in-depth interviews as the main data collection technique. In addition to these interviews, participatory observations and document content analysis were also conducted. The data collection instruments consist of interview guidelines and observation protocols. To ensure data validity, the study applies source triangulation, which involves comparing the information gathered from various informants and corroborating it with documents and observations. Data analysis was performed inductively through an interactive method that includes data reduction, data presentation, drawing conclusions, and verification. The findings indicate that the management and empowerment strategies at LazisMU are centered on providing business financial assistance to Mustahik with entrepreneurial ventures, as well as offering educational scholarships for university students. This research provides valuable insights and recommendations for other zakat management institutions, suggesting ways to enhance their operational performance and more effectively empower their beneficiaries through targeted financial and educational support initiatives.